The effect of slag composition and curing duration on the chloride ingress resistance of slag-blended cements. Issue 5 (16th March 2018) - Ogirigbo, Okiemute Roland; Black, Leon
Abstract : This paper reports the influence of varying curing durations on the chloride ingress resistance of slag blends. Samples were prepared by combining two slags (S1 and S2) with CEM I 52·5R cement at 30% by weight of slag. Mortar samples were cured for either 7 or 28 d, before being exposed to a 3% sodium chloride solution. Samples were subjected to two chloride exposure conditions (either complete submersion or a cyclic 6 h wetting and drying cycle). Depths of free chloride penetration as well as total and water-soluble chloride contents were measured for the exposed samples. Samples cured for 28 d before exposure showed far better resistance to chloride ingress than those cured for 7 d. The cement–slag blend with S1, having an alumina content of 12·23%, performed better than the blend with S2 (alumina content of 7·77%), especially for samples cured for 7 d. This was attributed to the higher basicity of S1. However, when the samples were cured for 28 d, the difference between the performances of the slag blends became minimal. Despite this, the overall performance of the slag blends, which was compared against a CEM I 42·5R-type cement, was found to be better at both curing durations.